The upgrading of the doctors in medicine to the light of Phylosophy and Sociology of Education - Omar Cabezas; Arturo Pulido Díaz (Revista MENDIVE, 2015)
The Pha rmacology upgrading process to doctors in Medicine is intended to update their knowledge for the teaching learning - process, as they are part of pedagogical and educational groups. The upgrading process on Pharmacology prepares them for their two main funct ions: t he teaching and the medical care one s . Values are crucial in doctors ́ everyday work, because of their social work related to the use of drugs.